а) 12 в отношении 1 : 3
3+1=4 - всего частей
12/4=3 - в 1 части
1*3 : 3*3
3: 9б) 15 в отношении 2 : 3
2+3=5 - всего частей
15/5=3 - в 1 части
2*3 : 3*3
6: 9
в)48 в отношении 3 : 5
3+5=8 - всего частей
48/8=6 - в 1 части
3*6 : 5*6
18: 30
г) 100 в отношении 1: 1
1+1=2 - всего частей
100/2=50 - в 1 части
1*50 : 1*50
50: 50
2: 3
2+3=5 - всего частей
100/5=20 - в 1 части
2*20 : 3*20
40: 60
ответ: y ' = - lnx .
Пошаговое объяснение:
y = x( 1 - lnx ) ;
y ' = [ x( 1 - lnx ) ]' = x' * ( 1 - lnx ) + x * ( 1 - lnx )' = 1 * ( 1 - lnx ) + x *( 0 -1/x ) =
= 1 - lnx - 1 = - lnx ; y ' = - lnx .